2004
DOI: 10.2134/agronj2004.0812
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Nutritive Value of Summer Legumes as Influenced by Dairy Manure Compost and Competition with Crabgrass

Abstract: Warm‐season legumes have the potential to improve range and pasture value as well as provide wildlife feed and habitat but are often unable to compete with aggressive annual grasses on infertile, low‐P soils. A strip split‐plot design experiment was established on a Windthorst fine sandy loam (fine, mixed, thermic, Udic Paleustalf) under irrigation to evaluate legume herbage production and nutritive value in the 1999 and 2000 growing seasons in competition with crabgrass (Digitaria ciliaris Koetz.) and with da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…None of these are as yet widely recommended in cultivated pasture seed mixtures because of the lack of seedling vigour, low productivity and persistence, and anti‐quality factors (Posler et al. , 1993; Berg, 1996; Jackson, 1999; Nguluve et al. , 2004).…”
Section: What Needs Further Developmentmentioning
confidence: 99%
“…None of these are as yet widely recommended in cultivated pasture seed mixtures because of the lack of seedling vigour, low productivity and persistence, and anti‐quality factors (Posler et al. , 1993; Berg, 1996; Jackson, 1999; Nguluve et al. , 2004).…”
Section: What Needs Further Developmentmentioning
confidence: 99%
“…Under competition with C. sativa , faba bean genotypes had lower chlorophyll content in the leaves. Low chlorophyll content could be due to a deficiency in nitrogen uptake and low protein content (Nguluve et al ., ). In winter oilseed rape, the chlorophyll content was significantly and positively correlated with the seed protein content (Kessel, ).…”
Section: Discussionmentioning
confidence: 97%
“…Nguluve et al . () showed that legumes, such as Desmathus sp. and Macroptilium sp., had lower protein concentrations in vegetative parts under competition with grasses when compared with plots without competition, apparently due to a lower nitrogen uptake.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in forage quality may be explained by shifts in plant community composition and relative abundance, known to influence forage quality (Pirhofer-Walzl et al 2011). Compost amendment can increase grass competition with legumes (Nguluve et al 2004), and grasses have lower N and mineral content and greater lignin content than forbs (Knapp et al 2011). Forage species composition and relative abundance were not measured during this study but would help analysis and interpretation as well as provide a potential field indicator for forage quality.…”
Section: Discussionmentioning
confidence: 99%